Instructional materials for developing skills in writing - Quitzon, Beatriz Puzon 1932- (s.n], 1972)
This is an expansion of a term paper in Education 275, which aims to provide sufficient instructional materials by way of composition models and systematic drills in writing so that students could think and write clearly. The two writing skills this paper seeks to develop are the skill in different techniques of paragraph development and the skill in the sequencing of sentences.